RNA Isolation and Characterization Protocols - Rapley, Ralph; Manning, David L. (Methods in molecular biology, 1998)
to Isolating RNA -- Large and Small Scale RNA Preparations from Eukaryotic Cells -- An Improved Rapid Method of Isolating RNA from Cultured Cells -- Isolating RNA with the Cationic Surfactant, Catrimox-14 -- RNA Extraction from Formalin-Fixed and Paraffin-Embedded Tissues -- Extraction and Purification of RNA from Plant Tissue Enriched in Polysaccharides -- Isolation of Plant Mitochondrial RNA from Green Leaves -- Extraction of RNA from Fresh and Frozen Blood -- Isolation of Total RNA from Bacteria -- Isolation of Total RNA from Tissues or Cell Lines -- Isolation of Messenger RNA -- UV Spectrophotometric Analysis of Ribonucleic Acids -- Formaldehyde Gel Electrophoresis of Total RNA -- Preparation of RNA Dot-Blots -- Nonradioactive Northern Blotting -- The Use of RNA Probes for the Analysis of Gene Expression -- Analysis of RNA by Northern Blotting Using Riboprobes -- RNA Quantitative Analysis from Fixed and Paraffin-Embedded Tissues -- Quantitative Analysis of RNA Species by PCR and Solid-Phase Minisequencing -- Preparation of Tissue Sections and Slides for mRNA Hybridization -- Detecting mRNA in Tissue Sections with Digoxigenin-Labeled Probes -- One-Tube RT-PCR with Sequence-Specific Primers -- Identification of Differentially Expressed Genes by Nonradioactive Differential Display of Messenger RNA -- Characterization of RNA Using Continuous RT-PCR Coupled with ELOSA -- Gene Expression Analysis by CD-RT-PCR Eric de Kant -- Primer Extension Analysis of mRNA -- S1 Mapping Using Single-Stranded DNA Probes -- Measurements of Rate of Transcription in Isolated Nuclie by Nuclear "Run-Off" Assay -- Transcription In Vitro Using Bacteriophage RNA Polymerases -- In Vitro Translation of Messenger RNA in a Rabbit Reticulocyte Lysate Cell-Free System -- In Vitro Translation of Messenger RNA in a Wheat Germ Extract Cell-Free System -- The Xenopus Egg Extract Translation System -- Purification and Characterization of Viral dsRNA Genome Profiles by Crosshybridization.
Keywords: Aufsatzsammlung; Isolierung; RNS; Analyse